Inducing molecular reactions by selective vibrational excitation of a remote antenna with near-infrared light - Nunes, Cláudio M (2021)
We demonstrate here that selective vibrational excitation of a moiety, remotely attached in relation to the molecular reaction site, might offer a generalized strategy for inducing bond-breaking/bond-forming reactions with exquisite precision. As a proof-of-principle, the electrocyclic ring-expansion of a benzazirine to a ketenimine was induced, in a cryogenic matrix, by near-IR light tuned at the overtone stretching frequency of its OH remote antenna. This accomplishment paves the way for harnessing IR vibrational excitation as a tool to guide a variety of molecular structure manipulations in an exceptional highly-selective manner.